Pengaruh Motivasi Hedonisme dan Korean Wave Terhadap Impulsive Buying dengan Personal Branding Syariah Sebagai Variabel Intervening - Ramadhani Aulia Faturrazaq; I Made Sukresna (Jurnal Ilmiah Ekonomi Islam, 2023)
In the last two decades, Korean culture has experienced rapid development and has spread globally to various countries in the world, including Indonesia. The Korean Wave or in Korean usually called hallyu according to (Suh, Cho, & Kwon, 2006) is defined as "The rapid expansion of the Korean contemporary culture and cultural products throughout East Asia since the mid-1990's" or the expansion of Korean culture and products carried out in a large and rapid manner to East Asia in the mid-1990s. The massive development of information technology due to globalization is the main factor in the growth of public enthusiasm for the Korean Wave in Indonesia itself, especially among the younger generation (millennial generation) in the 2000s and the current young generation (generation Z). The aim of this research is to determine the influence of Hedonistic Motivation and the Korean Wave on Impulsive Buying with Personal Branding as an intervening variable. This research uses quantitative methods to test and search for evidence for the hypotheses that have been established. As many as 133 respondents were generated from the questionnaire distributed by researchers. The purposive sampling method was chosen in this research because the researcher determined the criteria and attributes of the individuals who were used as research respondents. Judging from the objectives of the research conducted, it is known that hedonistic motivation is related to impulsive buying, but the Korean wave and personal branding are not related or have an influence on impulsive buying. However, hedonic motivation and Korean wave each have a significant influence on personal branding. The research model construct focuses on impulsive buying among consumers who are fans of K-pop groups in Indonesia. The research was carried out with a sample size that was stated to be sufficient using PLS SEM as a data processing tool. Next, findings related to the research hypotheses presented will be revealed.